The Effect of Working Capital Turnover on Profitability at PT. Arwana Citra Mulia Tbk Period 2015-2022 - Suratminingsih Suratminingsih (Doktoral Ilmu Manajemen, Universitas Pasundan, 2023)
This study aims to examine the influence of return on assets on stock prices at PT Chandra Asri Petrochemical Tbk for the period of 2011-2022. The research method employed is explanatory research. Statistical analysis techniques such as regression analysis, correlation analysis, determination analysis, and hypothesis testing were used. The findings of this study reveal that the return on assets variable obtained an average value of 55.58%. Meanwhile, the stock price variable obtained an average value of 19.67%. The return on assets has a positive and significant impact on stock prices, as indicated by the regression equation Y = -51.855 + 1.287X. The correlation coefficient of 0.620 indicates a strong relationship between the two variables. The coefficient of determination of 38.5% suggests that approximately 38.5% of the variation in stock prices can be explained by the variation in return on assets. The hypothesis testing also yields a significant result, with a significance value of 0.031 < 0.05. Based on these findings, it can be concluded that return on assets has a significant influence on stock prices at PT Chandra Asri Petrochemical Tbk. This suggests that the financial performance of the company, represented by the return on assets, can affect the value of the company's stocks. These findings provide valuable insights for stakeholders in making investment decisions and managing risks related to the stocks of PT Chandra Asri Petrochemical Tbk.